Implementation of Moving Average for Forecasting Inventory Data Using CodeIgniter - Fikri Hamidy; Ikbal Yasin (Journal of Data Science and Information Systems, 2023)
The purpose of this study is to be able to apply a manual inventory forecasting system with the moving average method in order to speed up the decision-making process and be able to minimize the error rate in calculating stock in the warehouse. The results of inventory forecasting in 2023 have an average of 192 for 116 BR animal feed items. Based on the results of calculating the average amount, a satisfaction level of 3,825 was obtained and if you follow the reference of Kaplan and Norton satisfaction level, the conclusion that can be drawn is that the level of user satisfaction with the inventory application is included in the satisfied category. So that the indications shown are positive from the PIECES model, namely users are satisfied with this inventory application.